Climate Policy 2015: Reports from the Congressional Trenches - Tisher, Sharon; Mills, Peter (Maine Policy Review, 2016)
The bipartisan commentary by Peter Mills and Sharon Tisher urges action in Congress to address the problem of climate change, and stems from interviews with Senator Susan Collins, Senator Angus King, and Congresswoman Chellie Pingree regarding their climate-related initiatives in 2015.